Proposed Strategy Improvement For Ngurah Rai International Airport (The Indonesian Journal of Business Administration, 2013)
The number of visitors to Bali is increasing. Indirectly its affect Ngurah Rai International Airport as one of the entrances to Bali to give a good service for their visitors and influence Balinese people about their fear of losing their culture due to other cultures. The analysis consists of Internal and External Analysis. The internal and external analysis consists of Marketing Mix, Value Chain Analysis, PESTEL and Questionnaire. The analysis shows that visitor feel unsatisfied with some of service that Ngurah Rai International Airport given, lack of transfer knowledge in internal organization, lack of capacity airport, lack of Balinese culture nuance. There are some strategy solutions is given to Ngurah Rai International Airport such as increase capacity in airport, provide sharing system for internal data process, provide good security check service, provide good service, indirectly create airport as a place of environment preservation and implementing Balinese culture.The implementation plan for strategy solution are doing cooperation with other party which have contribution to the airport services, cooperation with tourist attraction about culture and environment preservation, clarifying the prohibition of littering and smoking, cooperation with government about government regulation, perform an eco-airport trend and perform local art at the airport.Â Keywords: NgurahRai International Airport, Balinese culture, Eco tourism